Conserving the character of Jalan Tuanku Abdul Rahman / Azmi Abdul Rahman - Azmi, Abdul Rahman (Faculty of Architecture,Planning and Surveying, 1983)
We often see the visualisation of a major project in the city or even the renewal development of a major street or area. But what will happen, as usual, to portions of the project when they are parcelled out to different developers to undertake, and what will happen to the overall scheme in say thirty or forty years' time when every development is completed. The forces at work in our cities are so diverse, and the rate of social change has accelerated so rapidly, that it is most unlikely that such a large project, if it is constructed at all, will end up looking like the original design. All too often, the merij. of the published design derives from the architecture of the proposed buildings, rather than from any underlying coherence in the plan itself. What if the building is not placed at precisely the angle shown in the drawings? What if materials vary; what if changes in architectural taste occur? What if changes in function or economics force major changes in size or shape of buildings? Will the design still make sense...